
展开全部
f(x)
=x+1 ; x<0
=0 ; x=0
=x^2 ; x>0
let
u=x+1
du=dx
x=-2 , u=-1
x=0, u=1
∫(-2->0) f(x+1) dx
=∫(-1->1) f(u) du
=∫(-1->0) f(u) du +∫(0->1) f(u) du
=∫(-1->0) (u+1) du +∫(0->1) u^2 du
=(1/2)[(u+1)^2]|(-1->0) +(1/3)[u^3]|(0->1)
=(1/2)(1-0) +(1/3)(1-0)
=1/2 +1/3
=5/6
=x+1 ; x<0
=0 ; x=0
=x^2 ; x>0
let
u=x+1
du=dx
x=-2 , u=-1
x=0, u=1
∫(-2->0) f(x+1) dx
=∫(-1->1) f(u) du
=∫(-1->0) f(u) du +∫(0->1) f(u) du
=∫(-1->0) (u+1) du +∫(0->1) u^2 du
=(1/2)[(u+1)^2]|(-1->0) +(1/3)[u^3]|(0->1)
=(1/2)(1-0) +(1/3)(1-0)
=1/2 +1/3
=5/6
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询